2022
DOI: 10.1038/s41598-022-26565-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for predicting Mycoplasma pneumoniae pneumonia in adults

Abstract: The study aimed to explore predictors of Mycoplasma pneumoniae pneumonia (MPP) in adults and develop a nomogram predictive model in order to identify high-risk patients early. We retrospectively analysed the clinical data of a total of 337 adult patients with community-acquired pneumonia (CAP) and divided them into MPP and non-MPP groups according to whether they were infected with MP. Univariate and multivariate logistic regression analyses were used to screen independent predictors of MPP in adults and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…The radiological findings showed that the most common manifestation was patchy opacities, followed by bronchial wall thickening (more common in children). These findings are non-specific and similar to those reported in previous studies on MP [ 5 , 12 ]. Several researchers have proposed that the bronchial wall thickening could serve as a diagnostic indicator [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The radiological findings showed that the most common manifestation was patchy opacities, followed by bronchial wall thickening (more common in children). These findings are non-specific and similar to those reported in previous studies on MP [ 5 , 12 ]. Several researchers have proposed that the bronchial wall thickening could serve as a diagnostic indicator [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…The caregivers had an average age of 35.1 ± 4.6 years, and most of them were female. A plausible explanation is the differences in immunity and social activities between men and women, and the fact that mother in Chinese families tend to care for children more and have closer contact with them [ 6 , 12 ]. Both groups had similar clinical symptoms, with fever and cough being the most frequent on admission.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies have focused on children with Mycoplasma pneumoniae infection, the incidence of Mycoplasma pneumoniae infection in adults with community-acquired pneumonia has increased in recent years [14][15][16] . In this study, we used tNGS technology to analyze bronchoalveolar lavage uid samples to explore the differences in co-infection and pathogen spectrum between pediatric and adult patients.…”
Section: Resultsmentioning
confidence: 99%
“…С этой целью применимы такие доступные маркеры, как прокальцитонин и отношение СРБ/прокальцитонин >350 мкг/нг [42]. Последний показатель, по ограниченным данным, может свидетельствовать о микоплазменной пневмонии, тем более если при мультиспиральной компьютерной томографии выявлен феномен «дерево в почках» [43,44].…”
Section: правила постановки диагнозаunclassified